DIVERSIFYING UZBEKISTAN’S EXPORT MARKETS: THE POTENTIAL OF SOUTH AND SOUTHEAST ASIAN COUNTRIES - Shukhratbek Davron ugli Sapaev; Gulbakhor Matyakubovna Bakoeva (Modern American Journals, 2025)
This article examines the problem of Uzbekistan’s high geographical export concentration and explores how it can be reduced by developing new markets outside the CIS. An analysis of the current export structure shows that the Herfindahl–Hirschman Index (HHI) reveals a significant dependence on a limited group of partner countries, while revealed comparative-advantage (RCA) indices highlight product niches in which Uzbekistan is competitive (e.g., cotton, non-ferrous metals). Using principal-component analysis (PCA), we construct a composite priority score for prospective markets—India, Bangladesh, Indonesia and Vietnam—taking into account economic size, import demand, growth rates and trade barriers. The resulting scores are compared with those of Kazakhstan and Azerbaijan—countries with similar export profiles—to identify common trends and differences. The findings indicate that Uzbekistan’s exports are highly concentrated both regionally and by product, creating vulnerability to external shocks. Entering South and Southeast Asian markets could improve the resilience of its export activities. The paper concludes with policy recommendations for diversification: negotiating trade agreements, supporting non-commodity sectors, upgrading product-quality standards and improving logistics.
Keywords: Uzbekistan’s exports; market diversification; Herfindahl–Hirschman Index (HHI); revealed comparative advantage (RCA); principal-component analysis (PCA); trade barriers; South Asia; Southeast Asia.